2017
DOI: 10.1073/pnas.1617589114
|View full text |Cite
|
Sign up to set email alerts
|

Brain regions and functional interactions supporting early word recognition in the face of input variability

Abstract: Perception and cognition in infants have been traditionally investigated using habituation paradigms, assuming that babies' memories in laboratory contexts are best constructed after numerous repetitions of the very same stimulus in the absence of interference. A crucial, yet open, question regards how babies deal with stimuli experienced in a fashion similar to everyday learning situationsnamely, in the presence of interfering stimuli. To address this question, we used functional near-infrared spectroscopy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…Notably, whereas the superior temporal regions are affected by the immediate repetition of a sentence 54 , repetition at a longer time-scale of 14 s produces activation in the inferior frontal gyrus in three-month-old infants 55 . Moreover, a NIRS study in sleeping neonates revealed that a correlated activity between left-temporal and left-frontal regions, compatible with activation in the dorsal linguistic pathway, is crucial for word learning 56 . As for the hippocampus, activity has been reported in infants as young as 3-months when performing a visual sequence learning task, with no modulation by infant’s age 57 .…”
Section: Discussionmentioning
confidence: 94%
“…Notably, whereas the superior temporal regions are affected by the immediate repetition of a sentence 54 , repetition at a longer time-scale of 14 s produces activation in the inferior frontal gyrus in three-month-old infants 55 . Moreover, a NIRS study in sleeping neonates revealed that a correlated activity between left-temporal and left-frontal regions, compatible with activation in the dorsal linguistic pathway, is crucial for word learning 56 . As for the hippocampus, activity has been reported in infants as young as 3-months when performing a visual sequence learning task, with no modulation by infant’s age 57 .…”
Section: Discussionmentioning
confidence: 94%
“…The fNIRS arrays were designed so that responses could be recorded over auditory associative brain regions including the inferior frontal gyrus (IFG), middle and superior temporal regions and extending to the temporo‐parietal junction across both cohorts (Lloyd‐Fox et al, ). These regions have been previously linked with auditory repetition suppression and novelty detection in early infancy (Benavides‐Varela et al, ; Bouchon et al, ; Mahmoudzadeh et al, ; Nakano et al, ) and adulthood (Belin & Zatorre, ; Dehaene‐Lambertz et al, ), and subsequent recovery of response to novel speech (Benavides‐Varela et al, ; Bouchon et al, ; Dehaene‐Lambertz et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…In this study infants were awake, and this paradigm was presented as part of a battery of other fNIRS tasks. Therefore the design of previous studies (Benavides‐Varela et al, ; Nakano et al, ) was adapted with the intention of (a) increasing data retention, (b) utilizing a situation more similar to everyday learning situations (Benavides‐Varela et al, ), (c) creating a paradigm that would be more appropriate for application in a noisier and variable environment such as that often encountered in low‐resource global health research contexts (Sabanathan et al, ) and (c) allowing the investigation of responses in participants across a broad age range from 0 to 24 months of age. The paradigm employed a naturalistically presented and engaging sentence, spoken by a culturally appropriate adult (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, whereas the superior temporal regions are affected by the immediate repetition of a sentence (Dehaene-Lambertz, 2017), repetition at a longer time-scale of 14 seconds produces activation in the inferior frontal gyrus in three-month-old infants (Dehaene-Lambertz et al, 2006). Moreover, a NIRS study in sleeping neonates revealed that a correlated activity between left-temporal and leftfrontal regions, compatible with activation in the dorsal linguistic pathway, is crucial for word learning (Benavides-Varela et al, 2017). As for the hippocampus, activity has been reported in infants as young as 3-months when performing a visual sequence learning task, with no modulation by infant's age (Ellis et al, 2020).…”
Section: Putative Underlying Neural Networkmentioning
confidence: 99%